2006
DOI: 10.1128/iai.01741-05
|View full text |Cite
|
Sign up to set email alerts
|

The Actinobacillus actinomycetemcomitans Ribose Binding Protein RbsB Interacts with Cognate and Heterologous Autoinducer 2 Signals

Abstract: Autoinducer 2 (AI-2) produced by the oral pathogen Actinobacillus actinomycetemcomitans influences growth of the organism under iron limitation and regulates the expression of iron uptake genes. However, the cellular components that mediate the response of A. actinomycetemcomitans to AI-2 have not been fully characterized. Analysis of the complete genome sequence of A. actinomycetemcomitans (www.oralgen.lanl.gov) indicated that the RbsB protein was related to LuxP, the AI-2 receptor of Vibrio harveyi. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 43 publications
4
79
0
1
Order By: Relevance
“…Introduction of S-adenosylhomocysteine hydrolase to A. actinomycetemcomitans, which restores the metabolism of SAM in the absence of LuxS, did not complement the luxS mutation unless AI-2 was added in trans. The biofilm growth defect was also observed in RbsB-and LsrB-deficient backgrounds, as well as with wild-type A. actinomycetemcomitans in the presence of ribose, which competes with AI-2 for binding to RbsB (21). Together, these results suggest that AI-2 itself is required for A. actinomycetemcomitans biofilm growth and that RbsB and LsrB function as AI-2 receptors in A. actinomycetemcomitans.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Introduction of S-adenosylhomocysteine hydrolase to A. actinomycetemcomitans, which restores the metabolism of SAM in the absence of LuxS, did not complement the luxS mutation unless AI-2 was added in trans. The biofilm growth defect was also observed in RbsB-and LsrB-deficient backgrounds, as well as with wild-type A. actinomycetemcomitans in the presence of ribose, which competes with AI-2 for binding to RbsB (21). Together, these results suggest that AI-2 itself is required for A. actinomycetemcomitans biofilm growth and that RbsB and LsrB function as AI-2 receptors in A. actinomycetemcomitans.…”
supporting
confidence: 57%
“…2B) and also significantly reduced the rate of AI-2 depletion from solution by intact cells (40). We also previously showed that ribose and AI-2 compete for the same binding site of RbsB (21), suggesting that ribose may block AI-2 interaction with RbsB and LsrB and interfere with AI-2-dependent phenotypes. To determine if ribose inhibits A. actinomycetemcomitans biofilm growth, biofilms of strain JP2 were generated by feeding adherent cells with BHI containing 50 mM or 100 mM ribose.…”
Section: Vol 75 2007 Ai-2 Controls a Actinomycetemcomitans Biofilmmentioning
confidence: 99%
“…We hypothesize that the reduction in AI-2 activity is due to an active uptake system such as that which exists in Salmonella typhimurium and Aggregatibacter actinomycetemcomitans. These species can remove AI-2 from solution through the expression of ABC-type transporters (James et al, 2006;Shao et al, 2007;Taga et al, 2001Taga et al, , 2003. Assuming that the reduction of AI-2 activity by S. gordonii DL1 and S. oralis 34 is also due to the removal by transporters, the difference in rates of removal along with different rates of production of AI-2 will contribute to the amount of AI-2 that is bioavailable for cell-cell communication.…”
Section: Discussionmentioning
confidence: 99%
“…Spojevi iz češnjaka, ekstrakta vanilije, papra i halogenirani furanoni koje proizvodi morska alga Delisea pulchra pokazali su quorum sensing inhibitorna svojstva (37 -44). Istraživanja su također pokazala da dodatak spojeva sličnih ribozi u kulturu Aggregatibacter actinomycetemcomitans negativno utječu na formaciju biofilma, s obzirom na to da receptori autoinduktor-2 iskazuju određenu homolognost receptorima koji vežu ribozu, zbog čega riboza djeluje kao receptorni antagonist (45). Dokazano je i da halogenirani furanoni, konkretno furanoni s bromom, negativno djeluju na formaciju biofilma Porphyromonas gingivalis bez utjecaja na rast bakterijske populacije (46).…”
Section: Quorum Sensing and Bacterial Iron-uptakeunclassified